Correlation between parity and metabolic syndrome in Chinese women aged 40 years and older: the Reaction study - Qian Xie (BMC, 2021)
Abstract Aims The purpose of the present study was to investigate the correlation between the number of live-birth pregnancies and metabolic syndrome (MetS) in Chinese women according to menstruation history. Methods Registry data for all pregnancies in a cohort of 6157 Chinese women aged 40 years or older were obtained and the number of live-birth pregnancies were enumerated. We defined MetS using five criteria: impaired insulin metabolism and glucose tolerance, obesity in the abdominal area, dyslipidemia, and hypertension. Multivariate logistic regression analysis was conducted to assess potential risk factors for MetS. Postmenopausal women with three or more of live-birth pregnancies had the highest prevalence of MetS (P < 0.05). Results Among the 6157 females aged 40 years or older in Luzhou city, 2143 (34.8%) participants had incident MetS. The number of live-birth pregnancies was significantly correlated with age and fasting blood glucose (FBG) level (P < 0.05). The prevalence of MetS increased with the number of live-birth pregnancies (P < 0.01), and the frequency in postmenopausal women was significantly higher than that in premenopausal women (P < 0.001). In the binary logistic regression model, menopausal status [OR = 0.343 (0.153–0.769), P < 0.001] were significantly associated with an increased risk of MetS. Conclusions The number of live-birth pregnancies is correlated with an increased risk of MetS in Chinese women aged 40 years and over, especially in postmenopausal women. Greater attention should be paid to postmenopausal women who have had multiple live-birth pregnancies with a view to intervening early to prevent related diseases.